Online Learning Problems At State Elementary School 5 Sawojajar - Mauliadini, Almira Zahra (LPPM-ITEBA, 2024)
The goal of this research is to detail the challenges encountered by educators and students alike when attempting to learn online during the COVID-19 epidemic, as well as the ways in which these challenges were mitigated. Public Elementary School 5 Sawojajar Malang is the site of this descriptive qualitative study. Interviews and a review of relevant literature were the primary methods of data collecting for this research. The purpose of this research was to identify many issues with online education during the COVID-19 epidemic. Teachers have challenges in online learning due to the lack of control and assessment tools available to them. Some students are less engaged in their learning, leading to boredom and apathy, and there is a shortage of facilities that may be utilized for online learning